Influence of plant density and growth habit of common bean on leaf area development and N accumulation. Issue 5 (3rd September 2019) - Michelangeli, José A. Clavijo; Ricaurte, Jaumer; Sinclair, Thomas R.; Rao, Idupulapati M.; Beebe, Stephen E.
ABSTRACT: Crop yield requires leaf area to intercept solar radiation and to undertake photosynthesis, both of which depend on nitrogen (N) accumulation. Further, the amount of accumulated plant N at the beginning of seed fill serves as the reservoir for N required in synthesizing the proteins in developing seeds. For common bean ( Phaseolus vulgaris L.), resolution of the basic characteristics limiting production is challenging because of variation in plant growth-habit and in wide-ranging plant spacing. Field experiments were undertaken at two low-latitude locations with three plant growth-habit types and six plant densities to measure canopy leaf area and leaf N accumulation at the beginning of seed fill. Plant spacing of 20 plants m −2 or more was sufficient to result in equal leaf area and N accumulation for all six plant genotypes at each location. However, the low-altitude, higher-temperature location had lower accumulated leaf N and yield than the high-altitude, cooler-temperature location. These results indicate attention needs to be given to physiological or agronomic approaches to overcome the negative impact of high temperature on N accumulation by common bean.